2018
DOI: 10.1038/s41467-018-07060-w
|View full text |Cite
|
Sign up to set email alerts
|

REX1 is the critical target of RNF12 in imprinted X chromosome inactivation in mice

Abstract: In mice, imprinted X chromosome inactivation (iXCI) of the paternal X in the pre-implantation embryo and extraembryonic tissues is followed by X reactivation in the inner cell mass (ICM) of the blastocyst to facilitate initiation of random XCI (rXCI) in all embryonic tissues. RNF12 is an E3 ubiquitin ligase that plays a key role in XCI. RNF12 targets pluripotency protein REX1 for degradation to initiate rXCI in embryonic stem cells (ESCs) and loss of the maternal copy of Rnf12 leads to embryonic lethality due … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
73
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(73 citation statements)
references
References 35 publications
0
73
0
Order By: Relevance
“…[ 67 ] Rnf12 activates Xist by targeting the autosomally encoded XCI repressor and pluripotency factor, Rex1 for degradation ( Figure 5 a). [ 25,68 ] Rnf12 clearly functions as a dose‐dependent Xist activator, as its overexpression in male cells results in ectopic XCI, and is rapidly silenced by Xist. [ 67 ] Its heterozygous deletion in females, however, does not abolish, but only delay XCI.…”
Section: Candidate Regulators and Mechanismsmentioning
confidence: 99%
“…[ 67 ] Rnf12 activates Xist by targeting the autosomally encoded XCI repressor and pluripotency factor, Rex1 for degradation ( Figure 5 a). [ 25,68 ] Rnf12 clearly functions as a dose‐dependent Xist activator, as its overexpression in male cells results in ectopic XCI, and is rapidly silenced by Xist. [ 67 ] Its heterozygous deletion in females, however, does not abolish, but only delay XCI.…”
Section: Candidate Regulators and Mechanismsmentioning
confidence: 99%
“…As RNF12 SR-motif phosphorylation is required for efficient substrate ubiquitylation and target gene regulation, we sought to define the downstream molecular pathway. The REX1 transcription factor substrate plays a critical role in RNF12-dependent regulation of Xist gene expression and Xchromosome activation (Gontan et al, 2012;Gontan et al, 2018). Thus, we hypothesised that REX1 ubiquitylation and degradation regulates additional genes, providing a mechanism by which RNF12 modulates neural gene expression.…”
Section: The Srpk-rnf12 Pathway Regulates Gene Expression By Promotinmentioning
confidence: 99%
“…In light of these results, we tested whether the RNF12 SR-motif is required for efficient degradation of nuclear substrates. A major substrate of RNF12 is the REX1/ZFP42 transcription factor, which mediates RNF12 function in X-chromosome inactivation (Gontan et al, 2012;Gontan et al, 2018). Increased REX1 protein levels are observed in RNF12 4xSA KI and RNF12 ΔSR-KI mESCs ( Figure 3D), as well as RNF12 W576Y-KI mESCs harbouring a catalytic mutant.…”
Section: Rnf12 Sr-motif Phosphorylation Drives Nuclear Anchoringmentioning
confidence: 99%
“…Studies on in vitro differentiated embryonic stem cells have shown that RLIM stimulates random XCI through degradation of REX1 that inhibits Xist (X inactivation specific transcript) transcription [8]. Very recently, Gontan and collaborators have shown that RLIM mediated REX1 degradation is a critical event in imprinted XCI, as the lethal phenotype of Rnf12 -/+ and Rnf12 -/- females is rescued in a mutant Rex1 background [9]. Of interest a maternally transmitted Rlim deletion causes not only a complete loss of female carriers because of defective imprinted XCI, but also about half of their male KO pups [9].…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, Gontan and collaborators have shown that RLIM mediated REX1 degradation is a critical event in imprinted XCI, as the lethal phenotype of Rnf12 -/+ and Rnf12 -/- females is rescued in a mutant Rex1 background [9]. Of interest a maternally transmitted Rlim deletion causes not only a complete loss of female carriers because of defective imprinted XCI, but also about half of their male KO pups [9]. Similar results have been observed in an earlier study using conditional Rlim KO in oocytes [7].…”
Section: Introductionmentioning
confidence: 99%